(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
The target of this work is to systematize available information on literature about organization and conduction of therapeutic process with children, according to the Behavior Analysis presuppositions. The work presents a definition of psychotherapy process, including phases and organization of tasks. It also discusses the child-therapy characteristics that require different organization and systematization. Finally, a suggestion is presented on the sequential systematization of directions to the conduction of behavioral psychotherapy process with children. The proposal is to briefly present a diagrammatic configuration after a step-by-step description of the process’ conduction, including, from the first contact with the child, to the procedures to the disconnection of the therapy. The expectation is that the suggested model aids in the comprehension of conduction process and for the decision’s choice in Child Psychotherapy.